Cultural diversity and plant-level productivity - Michaela Trax; Stephan Brunow; Jens Suedekum (Heinrich Heine University Düsseldorf, Düsseldorf Institute for Competition Economics (DICE), 2013)
Using comprehensive data for German establishments, we estimate plant-evel production functions to analyze if cultural diversity affects total factor productivity. We distinguish diversity in the establishment's workforce and in the aggregate labor force of the region where the plant is located. We find that a larger share of foreign workers . either in the establishment or in the region . does not affect productivity. However, there are spillovers associated with the degree of fractionalization of the group of foreigners into different nationalities. The aggregate level is, quantitatively, at least as important for productivity as the workforce composition inside the establishment.
Keywords: R23; J21; J31; 330; cultural diversity; plant-level productivity; knowledge spillovers